RISK FACTORS FOR UNRELIABLE EYEWITHNESS EVIDENCE - PUSHPA KUMARI (International Journal of Multidisciplinary Research and Studies, 2021)
Accuracy in eyewitness testimonies is crucial and the success and direction of criminal investigations rely heavily on the details given. Also, eyewitness testimonies have a large bearing on court decisions and the fate of people’s lives. The justice system places a lot of emphasis on eyewitness testimonies, so understanding memory recall and factors possibly affecting it is important. It has been a general consensus that eyewitness testimony is highly unreliable and it tends to cause problems for many cases. This can be observed in the reported 70% of the now more than 300 DNA exonerations of wrongfully convicted individuals (Wixted et al., 2015). The goals of this study is to alleviate those problems and provide concrete answers for eyewitness testimonies. The study will explore many aspects that are taken into account in eyewitness testimony. Many studies exploring memories, and how they are retrieved have been conducted. These studies have demonstrated that memories are constantly being formed and stored throughout the brain. Many factors have been explored in order to understand their effect on memory recall. The temperament of individuals has been linked to influence memory. Personality traits and moods can also have an effect on memory recall. The manner in which law enforcement conducts interviews can also influence someone’s memory recall. Gender differences have also been found during eyewitness account reports. It is important to understand as many factors as possible pertaining to eyewitness testimonies because of the importance it holds within the justice system.